REFINING THE DIAGNOSIS: A CASE REPORT ON THE ROLE OF FISH IN DETECTING SUBTLE MOSAIC KLINEFELTER SYNDROME - Wildan, Ardy; Firdausa, Sarah; Yunir, Em (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Mosaic forms of Klinefelter syndrome (KS) can pose a diagnostic challenge, particularly in patients with a normal male phenotype and unremarkable hormonal profiles. While conventional karyotyping is a widely used first-line tool for detecting chromosomal abnormalities, its sensitivity is limited in identifying low-level mosaicism, which may result in false-negative or misleading interpretations. Fluorescence in situ hybridization (FISH), offering higher resolution and the ability to analyze hundreds of interphase nuclei, can uncover subtle chromosomal abnormalities that significantly impact clinical decision-making. CASE A 34-year-old male presented with concerns about delayed pubertal development, minimal axillary and facial hair, and poor muscularity despite strength training. He reported onset of wet dreams at 16 years, with gradual deepening of the voice and scant body hair. Physical examination revealed a tall stature (187 cm), soft body habitus, mild gynecomastia, and bilaterally normal-sized testes (20 mL). Hormonal assays showed normal levels of testosterone (22.58 nmol/L), LH (3.6 mIU/mL), and FSH (4.0 mIU/mL). Initial chromosomal analysis revealed a mosaic 45,X[1]/46,XY[99] pattern, suggesting a potential diagnosis within the chromosomal disorders of sex development (DSD) spectrum. However, the discrepancy between the karyotype and the patient’s unequivocally male phenotype prompted further investigation using FISH. Analysis of 300 nuclei revealed 6% 47,XXY cells and 94% 46,XY cells, confirming a diagnosis of mosaic Klinefelter syndrome. Semen analysis demonstrated severe oligoasthenoteratozoospermia with only 1% morphologically normal sperm. CONCLUSION This case illustrates the limitations of conventional karyotyping in detecting low-level mosaicism and underscores the diagnostic value of FISH in cases where clinical findings and cytogenetic results appear discordant. By providing higher sensitivity, FISH can uncover clinically significant mosaic patterns, facilitating accurate classification within the DSD spectrum and informing appropriate counseling and reproductive planning.